An Enhance of Renew Source for Homes - Hamdani Hamdani; Zuraidah Tharo; Siti Anisah; Solly Aryza (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Implementation of a new source for residential homes, this study uses a baseline based on the availability of PV mini-grid equipment. The research method is carried out by direct measurement of PLTS devices. The solar power plant devices measured include a solar cell module, a solar charge controller (SCC) Inverter testing is done by connecting the battery to the inverter input, and the inverter output is connected to a 500-Watt load capacity. The inverter lasts for about 3 hours. It can be stated that the battery can provide energy of 3 days.